Pengembangan Flashcard Interaktif Berbasis Articulate Storyline 3 sebagai Media Pembelajaran Tema Sich Vorstellen untuk Keterampilan Menulis Bahasa Jerman - Permata, Nabila Gea Arda; Wahyuningsih, Fahmi (LATERNE, 2025)
The media development was motivated by the difficulty of tenth grade students in writing skills on the theme Sich Vorstellen, which was caused by the lack of mastery of sentence structure and verb conjugation based on the subject. In addition, German language is become part of the foreign language lesson in high school, especially for tenth grade students, so media is needed as a fun variation of learning. The formulation of the problem in this study was how were the development process and the feasibility of interactive flashcards based on Articulate Storyline 3 as a learning medium for Sich Vorstellen theme for German writing skills. This study aimed to determine the development process and feasibility of interactive flashcards. The method in this study was RnD with the ADDIE model, which was limited to the development stage. Data was obtained through the results of material expert and media expert validation sheet. The results of the validation sheet of material experts and media experts showed that the media obtained the same percentage of feasibility, namely 96%. It can be concluded that the media was considered very feasible to use as learning media.